Left ventricular hypertrophy in athletes and hypertensive patients. Issue 4 (1st March 2017) - Lovic, Dragan; Narayan, Puneet; Pittaras, Andreas; Faselis, Charles; Doumas, Michael; Kokkinos, Peter
Abstract : Systemic hypertension and physical exercise are both associated with cardiac adaptations. The impact is most prominent on the left side of the heart, which hypertrophies leading to left ventricular hypertrophy. This article reviews structural and functional cardiac changes seen in hypertensive and athlete's hearts.